2008
DOI: 10.1186/1477-7819-6-57
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and problems with CT lymphography in identifying the sentinel node in breast cancer

Abstract: Background: Combining a radioisotope with a dye-guided method is the best method for identification of the sentinel lymph nodes (SNs) in breast cancer. However, some institutions are limited to use of a dye-guided method alone. Recently, computed tomographic lymphography (CTLG) employing a nonionic contrast medium has achieved SN identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
(32 reference statements)
1
29
1
1
Order By: Relevance
“…For identification of SLN by CTLG, the patient age, tumor location, surgical biopsy, the tumor size and the presence or absence of lymph node metastasis have been reported to influence identification of the SLN [7,23,24]. In our patients' series, there was no significant related factor.…”
Section: Discussioncontrasting
confidence: 47%
“…For identification of SLN by CTLG, the patient age, tumor location, surgical biopsy, the tumor size and the presence or absence of lymph node metastasis have been reported to influence identification of the SLN [7,23,24]. In our patients' series, there was no significant related factor.…”
Section: Discussioncontrasting
confidence: 47%
“…The identification rate was improved from 95 to 98.8% by using CTLG. It was reported that the identification rates with the blue-dye method were improved from 84% to 100% by CTLG in cases in which the BMI was over 25 [5]. CTLG is a helpful method that improves the identification rate of SLNBs using the perioperative dyestaining method.…”
Section: Discussionmentioning
confidence: 96%
“…While occult metastases can be detected by SLNB, indirect lymphography with CT and MRI is a alternative promising technique to SLNB. Takahashi et al [7] used CT-LG to identify SLNs of 218 breast cancer patients. Nakagawa et al [19] used CT-LG to detect SLN metastases of the breast in 228 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect lymphography is a alternative method to identify SLNs. Indirect CT lymphography (CT-LG) with iodine contrast agent and MRI lymphography (MRI-LG) with gadolinium-containing contrast agents have the advantages of high sensitivity, excellent spatial resolution and low doses of contrast agent needed [7], and have been widely used in SLNB [8,9,10]. However, there have been few clinical applications to identify SLNs in head and neck tumors [11,12] because of the very short duration of enhanced imaging with iodine or gadolinium-containing contrast agents.…”
Section: Introductionmentioning
confidence: 99%